BEBERAPA SIFAT FISIK DAN KIMIA TANAH GAMBUT TERBAKAR DAN TIDAK TERBAKAR DI DESA SUNGAI BESAR KABUPATEN KETAPANG - Mintari, .; Astiani, Dwi; Manurung, Togar Fernando (Universitas Tanjungpura, 2019)
Peatlands is one of the ecosystem types in tropical rainforests. Peatland has very high conservation value and other functions such as the hydrological function carbon stocks, and biodiversity which is important for environmental comfort and animal life. The purpose of this study was to obtain information about the impact of fires on the physical and chemical properties of burning and non burning peat soils. This study carried out a field survey method with deliberate sampling (purposive sampling). The results showed that the physical and chemical properties of peat soil after a fire did not change, namely at soil temperature, air humidity was almost the same while the air temperature, soil moisture, pH, C-organic, depth, C/N (0-20 cm) has increased but not significantly. For the chemical properties of peat soil after fire there is an increase in the value of C-organic, CEC, phosphorus, sulfur,ash content, N-total depth (21-40 cm). this means that after fires the nutrients mostly affect peat soil. From the information on the nature of peat soil obtained in land restoration studies to use qualitative soil after burning.Keywords: Burn, chemical pea soil, Peatlands, Physicalpeat soil.